2019
DOI: 10.1016/j.nmni.2018.10.009
|View full text |Cite|
|
Sign up to set email alerts
|

Treponema species enrich the gut microbiota of traditional rural populations but are absent from urban individuals

Abstract: There is a significant gap in our knowledge of the microbe–host relationship between urban and traditional rural populations. We conducted a large-scale study to examine the gut microbiota of different traditional rural and urban lifestyles in human populations. Using high-throughput 16S ribosomal RNA gene amplicon sequencing, we tested urban French, Saudi, Senegalese, Nigerian and Polynesian individuals as well as individuals living in traditional rural societies, including Amazonians from French Guiana, Cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 41 publications
6
69
0
Order By: Relevance
“…However, as our analyses are limited to the genus level, it is unclear if these infants and young children carried pathogenic species. Finally, data show that Treponema is enriched in many rural populations leading traditional lifestyles, is transmitted between humans and animals, and is absent among populations living in urban settings, which might be due, in part, to the ubiquitous use of antibiotic among the latter (Angelakis et al, ). Our finding that differences in the abundance of Treponema were restricted to the two older age groups may be related to increased contact with domestic animals among older children.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our analyses are limited to the genus level, it is unclear if these infants and young children carried pathogenic species. Finally, data show that Treponema is enriched in many rural populations leading traditional lifestyles, is transmitted between humans and animals, and is absent among populations living in urban settings, which might be due, in part, to the ubiquitous use of antibiotic among the latter (Angelakis et al, ). Our finding that differences in the abundance of Treponema were restricted to the two older age groups may be related to increased contact with domestic animals among older children.…”
Section: Discussionmentioning
confidence: 99%
“…The Treponema genus contains mostly non-pathogenic species commonly associated with the mammalian intestine and oral cavity [60]. Treponema species seem to be under particular negative selection forces in Westernized populations as multiple studies found them at much higher abundance and prevalence in non-Westernized populations [7,11,54,61,62], and they were also identified in ancient coprolites [19], and dental calculus of the Iceman mummy [63]. To better study its diversity and host association, we investigated the phylogeny of this genus considering all the genomes from NHPs and humans currently available (Fig.…”
Section: Closely Phylogenetically Related Treponema Species Have Diffmentioning
confidence: 99%
“…Phascolarctobacterium, a propionate and acetate producer that has been shown to exert beneficial effects on its host 54,63,64 , appear to be abundant across both sites. A recent study comparing various industrialized, urban populations to traditional rural societies including Congolese Pygmies,…”
Section: Discussionmentioning
confidence: 99%
“…Alistipes, a top ten genus in the Soweto cohort in terms of relative abundance ( Figure 4D), showed significantly higher differential abundance in Bushbuckridge ( Figure 5C), indicating that the greater diversity in Bushbuckridge may have reduced its significance relative to other taxa in Bushbuckridge ( Figure 4F). Some of the other taxa associated with Bushbuckridge include the polysaccharide-degrading Comparing the microbiomes of the combined obese group (Bushbuckridge and Soweto) with their leaner counterparts revealed Treponema, a previously identified hallmark taxon associated with the traditional African microbiome 7,53,54 , and Clostridium_IV, a butyrate producer, to be more abundant in the lean category ( Figure 6C). Conversely, Barnesiella, Coraliomargarita, Gemmiger, Weissella, Veillonella, Parabacteroides, Oscillibacter, Acetanobacterium and Alloprevotella were among the differentially abundant taxa associated with the obese group ( Figure 6C).…”
Section: Cohort-wide Analysismentioning
confidence: 94%
See 1 more Smart Citation